Development of ALAMEDIA Interactive Multimedia Based on Articulate Storyline to Improve Learning Outcomes in Science for Fourth Grade Students - Alya Putri Maradika Ningrum; Ika Ratnaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Natural and Social Sciences (IPAS) is a compulsory subject in the Merdeka Curriculum that students must master. However, limitations in the use of learning media, particularly in the areas of natural resources and landscapes, are one of the factors contributing to students' low understanding of these topics. Therefore, this study aims to design and develop an interactive multimedia tool based on Articulate Storyline for fourth-grade students, with a focus on the topics of natural resources and landscape. The research uses a Research and Development (R&D) approach with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects are fourth-grade students at SD Negeri Sudirman, Ambarawa District, Semarang Regency, in the 2024/2025 academic year. The validation results from subject matter and media experts indicated that the developed media achieved a feasibility score of 93%, categorized as highly feasible. The practicality assessment reached 98%, indicating that the media is very easy to use. The effectiveness test using a t-test yielded a significance value below 0.05, indicating a significant difference between pretest and posttest scores. Additionally, the N-gain test showed an improvement in learning outcomes in the moderate category, with a score of 0.5505 on the small scale and 0.5620 on the large scale. Teachers and students also gave very positive feedback on the media. Therefore, it can be concluded that the interactive multimedia ALAMEDIA based on Articulate Storyline is effective, feasible, and practical in improving the learning outcomes of fourth-grade students in Science.